Performance of Illumina® BovineHD BeadChip in genotyping Indian riverine buffalo breeds - SHAH, HEENA; SUDHAKAR, A; DONTHULA, SANDEEP KUMAR; POOJARA, HARDIK; GAJJAR, SWAPNIL; SAHA, SUJIT; NAYEE, NILESH (The Indian Journal of Animal Sciences, 2022)
The current study tested the suitability of Illumina® BovineHD BeadChip in genotyping three riverine breeds of buffalo viz. Jaffarabadi, Murrah and Mehsana. Of the 777962 SNPs, 670955 SNPs were called in all animals and only 13150 SNPs were found to be polymorphic at a call rate of 90%, and had Minor Allele Frequency (MAF) greater than 0.05. The average Minor Allele Frequency (MAF) of polymorphic SNPs was 0.23 and average expected heterozygosity (HE) of 0.321. Principal Component Analysis (PCA) revealed 2 different clusters where Murrah and Mehsana breeds clustered together, while Jaffarabadi breed formed a distinct cluster. Result obtained in this study indicated that the SNPs available in Illumina BovineHD BeadChip may not be good enough for studying population structure and genetic analyses in Indian buffalo breeds. Hence it might be necessary to develop a custom SNP marker panel for Indian riverine buffaloes.